Cloning, sequencing, and phenotypic analysis of laf1, encoding the flagellin of the lateral flagella of Azospirillum brasilense Sp7. - Moens, S (1995)
Azospirillum brasilense can display a single polar flagellum and several lateral flagella. The A. brasilense Sp7 gene laf1, encoding the flagellin of the lateral flagella, was isolated and sequenced. The derived protein sequence is extensively similar to those of the flagellins of Rhizobium meliloti, Agrobacterium tumefaciens, Bartonella bacilliformis, and Caulobacter crescentus. An amino acid alignment shows that the flagellins of these bacteria are clustered and are clearly different from other known flagellins. A laf1 mutant, FAJ0201, was constructed by replacing an internal part of the laf1 gene by a kanamycin resistance-encoding gene cassette. The mutant is devoid of lateral flagella but still forms the polar flagellum. This phenotype is further characterized by the abolishment of the capacities to swarm on a semisolid surface and to spread from a stab inoculation in a semisolid medium. FAJ0201 shows a normal wheat root colonization pattern in the initial stage of plant root interaction.